Safety Evaluation on a Fastening Device of an Agricultural By-Product Collector for Hard Flat Ground Driving - Jeong-Hun Kim; Markumningsih Sri; Ju-Seok Nam (Agriculture, 2022)
In this study, the static safety factor and fatigue life of fastening devices of an agricultural by-product collector were evaluated under hard flat ground driving conditions. The strain gage-based measurement system was constructed, and the strain gage was attached on the highest stress spot of the fastening devices derived from structural analysis. The static safety factor and fatigue life of the fastening devices were calculated using the measured strain values and by converting it into stress data. The two operating conditions are considered to be the loading part of the by-product collector, lifted and non-lifted. The results for all fastening devices showed that the static safety factor was larger than 1.0 and the fatigue life was much greater than the expected lifetime under both operating conditions. Therefore, it can be concluded that the fastening devices of the by-product collector can be operated reliably under hard flat ground driving conditions. In future work, we plan to evaluate the safety of the fastening devices in various actual orchard farm environments.